Knowledge and Perceptions of Elementary School Teacher Education Students on Educational Philosophy - Febrianto, Priyono Tri; Masitoh, Siti; Nursalim, Mochamad (Widyagogik, 2022)
Education is a very vital thing in human life. Educational philosophy is a philosophy that sees education as a process to humanize students. This study seeks to reveal how the knowledge of PGSD students about the philosophy of education and students' perceptions of the philosophy of education. This study uses quantitative methods with descriptive research type. Respondents in this study were 174 students. This study found that the source of knowledge of each elementary school teacher education student about educational philosophy was 60.3 percent, namely social media. Most elementary school teacher education students consider educational philosophy to be an important science. Most of the perceptions about the importance of educational philosophy are because it can provide a complete understanding of science and be able to use the knowledge possessed. Philosophy of Education is very important to be taught to PGSD students who will become educators. For this reason, it is necessary to develop an innovative and creative educational philosophy of education model.